Seasonal Changes of Host Use by Culiseta melanura (Diptera: Culicidae) in Central Florida. Issue 5 (13th April 2020) - West, Richard G; Mathias, Derrick K; Day, Jonathan F; Acevedo, Carolina; Unnasch, Thomas R; Burkett-Cadena, Nathan D
Abstract: The mosquito Culiseta melanura (Coquillett) is the primary enzootic vector of eastern equine encephalitis virus (EEEV), a zoonotic Alphavirus endemic to eastern North America. In its northern range, Cs. melanura is considered a strict avian biter, transmitting EEEV among susceptible birds in a cycle of enzootic amplification. In its southern range, however, Cs. melanura is more general in host use, feeding heavily upon birds but also reptiles and mammals. The goal of this study was to better understand how host use of Cs. melanura changes throughout the year in Florida, where year-round EEEV transmission is observed. Mosquitoes were sampled in 2018 from nine sites across three central Florida counties. In total, 213 Cs. melanura bloodmeals were identified by PCR consisting of 39 species of birds, reptiles, and mammals. Avian bloodmeals were prominent throughout the year (range = 30–85%), and songbirds were a large portion of identified bloodmeals (37.1%). Reptiles surpassed birds only in spring (April–June), and brown anole ( Anolis sagrei Duméril and Bibron, 1837 [Reptilia: Dactyloidae]) was the most commonly detected single host species (22.1% overall). Mammalian bloodmeals were mainly observed in summer, with humans being the most fed on mammal (12.7% overall). This study reveals that in southern foci of EEEV transmission, Cs. melanura host use varies throughout the year with reptiles providing the majority of blood meals in spring (51.3%), and birds are fed on more than other host groups during all other seasons (50.6–70.1%). In addition, feeding on mammals increases during summer months, which may implicate Cs. melanura in epizootic transmission in Florida.